2019
DOI: 10.1039/c9dt01236b
|View full text |Cite
|
Sign up to set email alerts
|

A mechanochemical route for the synthesis of VNbO5 and its structural re-investigation using structure solution from powder diffraction data

Abstract: VNbO5 with a revised space group P212121 versus Pnma has been successfully synthesized by a solvent-free mechanochemical route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In recent years, increasing attention has been paid to the synergistic effects of bimetallic oxides. Studies have shown that the active substances can be obtained in situ by the addition of bimetallic oxides during the ball milling and reaction process. For example, MgH 2 –Ni 3 (VO 4 ) 2 , prepared by Zang et al, could generate Mg 2 Ni and V 2 O 3 in situ after dehydrogenation, and it could release 4.5 wt % hydrogen at 250 °C within 30 min and absorb 2.3 wt % hydrogen at 50 °C within 60 min. Moreover, in the subsequent reaction process, Mg 2 Ni and V 2 O 3 remain stable and play a synergistic role.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing attention has been paid to the synergistic effects of bimetallic oxides. Studies have shown that the active substances can be obtained in situ by the addition of bimetallic oxides during the ball milling and reaction process. For example, MgH 2 –Ni 3 (VO 4 ) 2 , prepared by Zang et al, could generate Mg 2 Ni and V 2 O 3 in situ after dehydrogenation, and it could release 4.5 wt % hydrogen at 250 °C within 30 min and absorb 2.3 wt % hydrogen at 50 °C within 60 min. Moreover, in the subsequent reaction process, Mg 2 Ni and V 2 O 3 remain stable and play a synergistic role.…”
Section: Introductionmentioning
confidence: 99%